Historical Studies of Changing Fertility - Tilly, Charles (Book collections on Project MUSE., 2015)
The nine papers in this volume examine the historical experience of particular populations in Western Europe and North America in a search for the processes that change fertility patterns. The contributors' findings enable them to reevaluate some of the conflicting hypotheses that have been advanced for these changes. The authors stress the effects on fertility of changing mortality. Several theoretical discussions emphasize the importance both of the turnover in adult positions due to mortality and of the highly variable life expectancy of children. The empirical analyses consistently reveal strong associations between levels of fertility and mortality. On the other hand, some essays question whether variations in opportunities to marry acted as quite the regulator that Malthus and many after him have thought. In both preindustrial and industrial populations, fertility regulation within marriage emerges as the primary mechanism by which adjustment occurred. Originally published in 1978. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.